The Effect of STEAM-Based Learning on Critical Thinking, Creativity, and Collaboration Skills of Senior High School Students - Ramdhan, Dadan F; Rizza, Muhamad; Najuba, Hilyatun; Muharam, Muhammad Yusuf (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2026)
This study aims to examine the effect of STEAM-based learning (Science, Technology, Engineering, Arts, and Mathematics) on students' critical thinking, creativity, and collaboration skills in secondary education. Utilizing a quantitative survey design, the study involved 108 twelfth-grade students at SMA Telkom Bandung, Indonesia, selected through purposive sampling from classes that actively implement the STEAM approach. Data were collected using validated and reliable Likert-scale questionnaires and subsequently analyzed using descriptive statistics and simple linear regression at a 0.05 significance level. The findings indicate that STEAM-based learning has a significant positive effect on all three core competencies: critical thinking (t=13.120; R2=0.619), creativity (t=14.200; R2=0.655), and collaboration (t=12.106; R2=0.580). These results confirm that the integration of the arts into STEM education effectively strengthens students' cognitive, creative, and social dimensions simultaneously, establishing it as a highly relevant pedagogical model for 21st-century demands. The novelty of this research lies in its integrative analysis, which simultaneously examines three fundamental 21st-century competencies within a single research model in the context of Indonesian secondary education. This area remains underexplored compared to Western literature. This study provides a significant contribution by offering empirical evidence that the